Therapeutic Effect of Oral Bisphosphonates on Choroidal Neovascularization in the Human Eye - Shigeru Honda; Takayuki Nagai; Naoshi Kondo; Masahide Fukuda; Sentaro Kusuhara; Yasutomo Tsukahara; Akira Negi (Journal of Ophthalmology)
Purpose. Choroidal neovascularization (CNV) is often associated with age-related macular degeneration (AMD) and pathological myopia (PM). Bisphosphonates, the drug of choice to treat osteoporosis, have been recently reported to have anti-angiogenic effects. The purpose of this study is to investigate the therapeutic effects of oral bisphosphonates for CNV in humans. Methods. Thirty-six consecutive cases with CNV due to AMD or PM who declined anti-VEGF therapy were recruited. The patients were prescribed 5 mg of oral alendronates daily for 6 months. The best-corrected visual-acuity (BCVA), the lesion size in fundus photographs and fluorescein angiography, foveal thickness and total macular volume in optical coherence tomography were compared between pre- and post-treatment. Results. The mean BCVA of the patients was significantly improved after a months with the treatment in the AMD group. In the PM group, the mean BCVA was maintained up to 6 months with the treatment. The mean lesion size was significantly decreased by 3 months in both groups. The averages of foveal thickness and total macular volume were significantly reduced after 1 month of treatment in the AMD group.Conclusions. Oral bisphosphonate should be further investigated as a possible therapeutic and preventive drug for CNV due to AMD and PM.